ANALISIS PENGARUH KUALITAS PELAYANAAN TERHADAP KEPUASAN PELANGGAN MENURUT PERSPEKTIF ISLAM (Studi Pada Kantor Pelayanan Pelanggan Unit Sistem Penyediaan Air Minum Pusako Di Kampung Sungai Limau Kecamatan Pusako) - Yani, Putri Indra; Pirmansyah, Pirmansyah (STAI Sulthan Syarif Hasyim, 2024)
This study aims to determine the extent to which service quality affects customer satisfaction. In this study, service quality includes reliability, responsiveness, assurance, empathy, and tangibles. The approach used in this study is quantitative. This study uses a correlation research technique. The data collection technique used a questionnaire. The population in this study was customers of the Pusako SPAM Unit office. A sample of 90 respondents was taken. The sampling technique used was proportional random sampling. The data analysis technique used simple linear regression and hypothesis testing. The results of the study show that service quality affects customer satisfaction, as evidenced by the simple linear regression analysis Y = -7.414 + 0.658, where the constant value (a) is -7.414; this can be interpreted as if the service quality value is 0, then the customer satisfaction value is -7.414. The regression coefficient value of the customer satisfaction variable (b) is positive, namely 0.658; this can be interpreted as meaning that for every 1.00 increase in service quality, customer satisfaction will increase by 0.658. Based on the t-test, the calculated t-value is 7.801, while the table t-value is 1.662. Therefore, t calculated > t table (7.801 > 1.662) and the significance value is 0.000 < 0.05, so H0 is rejected and Ha is accepted. This means that service quality has a significant effect on customer satisfaction.